Exploring the Nexus between Transfer of Technology Obligations and the Promotion of Foreign Investments in Renewable Energy - Ghaziani, Mohammad Akefi; Ziaee, Seyed Yaser; Fazaeli, Mostafa (REVISTA QUAESTIO IURIS, 2023)
Renewable energies are among the alternatives for developing countries to fulfil their growing energy needs and meet the requirements of the energy transition. However, renewable energy deployment costs billions of dollars and many countries are not able to afford the costs and technologies required to launch and utilise them. Therefore, developing countries strive not only to attract investments but also to have access to modern renewable energy technologies to upgrade their technological capabilities to international levels. IIAs can contribute to this aim since they contain provisions for the transfer of technology. However insisting on the technology transfer obligations can ceteris paribus make foreign investors reluctant to invest, as there is a prevailing disagreement regarding who should bear the costs associated with sharing these technologies. It is in the light of these challenges that the question of how IIAs can contribute to the promotion of foreign investments in this sector is of high importance from both practical and academic points of view. This article sheds light on this dilemma by expounding on the concept of the transfer of technology and describing the major challenges to this process. It further analyses the pertinent clauses in IIAs and analytically underpins the relevant approaches.